ERRATA (Journal of Finance, 1977)
Also, Harry M. Markowitz, the author of “Investment for the Long Run: New Evidence for an Old Rule,” was inadvertently referred to as Henry M. Markowitz on the cover and in the index of the December 1976 issue of the Journal of Finance.